Tumbuhkan Investasi Masa Depan: Sosialisasi Pembuatan Portofolio Saham untuk Generasi Muda - Annisa Paramaswary Aslam; Achmad Yassin Zidan Akram Aslam; Khaidir Syahrul; Syarif Saddam Rivanie Parawansa; Nurul Fadilah Aswar (Vokatek: Jurnal Pengabdian Masyarakat, 2024)
This research discusses the effectiveness of socializing stock portfolio creation among young people as an effort to prepare for their financial future. The aim of this study is to explore the impact of stock investment socialization programs on the understanding, active participation in the capital market, and the development of financial skills among young people. The results of the research indicate that effective stock investment socialization enhances young people's understanding of the risks and potential gains involved in stock investment. Moreover, these programs also encourage their active participation in the capital market and foster the necessary financial skills to manage investment portfolios efficiently. In conclusion, integrating stock investment education into formal education    curricula, developing mentorship programs, and leveraging digital technology are strategic steps to enhance financial literacy among young people. Recommendations for further research include further exploration of inhibiting factors and expanding the scope of stock investment socialization programs across various communities.